Design and simulation of bio fluidic sensor based on photonic crystal - Gaddam Kesava Reddy, Rajini; Ashok kumar, Sharmila; Varadhan, Sankardoss (International Journal of Engineering and Technology, 2014)
Photonic crystals are materials patterned with a periodicity in dielectric constant in one, two and three dimensions and associated with Bragg scattering which can create range of forbidden frequencies called Photonic Band Gap (PBG). By optimizing various parameters and creating defects, we will review the design and characterization of waveguides, optical cavities and multi-fluidic channel devices. We have used such waveguides and laser nanocavities as Biosensor, in which field intensity is strongly dependent on the type of biofliud and its refractive index. This design and simulation technique leads to development of a nanophotonic sensor for detection of biofluids. In this paper, we have simulated sensing of biofliud in various photonic defect structures with the help of a numerical algorithm called Finite Difference Time Domain (FDTD) method. The simulation result shows the high sensitivity for the change in the bio-molecular structure. For developing the complete sensor system, we have to use the MEMS technologies to integrate on-chip fluidic transport components with sensing systems. The resulting biofluidic system will have the capability to continuously monitor the concentration of a large number of relevant biological molecules continuously from ambulatory patients. Keywords: FDTD, Photonic Crystals, Bio fluid Sensor, Optical Cavity.